THE PATHOPHYSIOLOGY OF CUTANEOUS MANIFESTATIONS RELATED TO COVID-19 - Mawardi, Prasetyadi (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2023)
Covid-19 is a respiratory infection caused by the newly emerging coronavirus. Covid-19 can also cause skin abnormalities, although the pathophysiology of manifestations of skin disorders associated with Covid-19 has not been understood with certainty. This study aims to discuss the pathophysiology of cutaneous manifestation related to Covid-19. The study was conducted based on literature and data mining related to Covid-19 using PubMed and Google Scholar. Eligible papers provided pathophysiology of cutaneous manifestations related to Covid-19. Papers not available in English were excluded. As a result of the presence of edema, vasodilation, and cellular infiltration, skin lesions such as rash, urticarial, or extensive purpura, or even thrombosis and haemorrhage, arise if damage to the vessels became severe. The pathophysiology of Covid-19-associated skin manifestations is estimated through some different mechanisms, such as lesions found in various Covid-19 patients, namely, the presence of varicella such as eruption, non-characteristic rash, and urticarial. Further studies are required to establish a Covid-19 diagnosis based on skin manifestations.